The All-Seeing Algorithm: Panopticon and Surveillance of the Docudrama “The Social Dilemma” - Rahma Dhian Karisma Putri; Andre Noevi Rahmanto; Sudarmo Sudarmo (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to analyze the concept of Michel Foucault’s panopticon in the modern digital context, as depicted in the docudrama The Social Dilemma. The research focuses on understanding the surveillance mechanisms of social media and their psychological impacts on user behavior. Methodology: This research uses a qualitative approach with content analysis as the primary method. The object of study is the docudrama The Social Dilemma on Netflix. Data collection involves observation, documentation studies, and literature reviews from Scopus.com and other websites to identify how digital surveillance is portrayed and its effects on users. Main Findings: The study finds that social media platforms use advanced surveillance algorithms to monitor, influence, and control user behavior. These mechanisms form a digital panopticon where users feel constantly watched, leading to behavioral adjustments. The psychological impacts include anxiety, depression, and addiction, particularly among teenagers, driven by the normalization of constant digital surveillance. Novelty/Originality of this study: This study uniquely applies Foucault’s panopticon theory to analyze the influence of digital surveillance depicted in The Social Dilemma. The novelty of this research lies in its application of Foucault’s panopticon theory to digital platforms, providing new insights into the psychological and behavioral consequences of algorithmic surveillance. However, the study is limited by focusing on a single docudrama, which may not comprehensively represent the full spectrum of digital surveillance practices. Future research should expand on this analysis by examining broader datasets or additional media to validate these findings.